Creating a sustainable quality improvement in hepatocellular carcinoma screening rates in a free access medical system; improved outcomes and lessons learned. Issue 3 (15th May 2020) - Brazeau, Michael; Owen, Samuel; Taylor, Douglas; Rosa, Cesar; Morales‐Cardona, Amilcar
Summary: Background: Hepatocellular cancer (HCC) screening is considered cost efficient when the annual risk of HCC is 0.2% or greater per the American Association for the Study of Liver Disease guidelines. Individuals at high risk are advised to complete hepatic imaging every 6 months. Individuals that meet this criteria include all patients with cirrhosis and HBsAG‐positive adults at high risk (Asian or black men over 40 and Asian Women over 50, have family history in first‐degree relative, or persons co‐infected with hepatitis D). The rate of compliance of this recommendation falls short in many practices. Methods: In an initial quality improvement the HCC screening compliance rate for our clinic was able to be improved from an overall rate of 53.7%‐78.8% by mailing out letters to patients when due for imaging. The project ended in April 2019, as it was deemed non‐sustainable. In July 2019 a review displayed that the compliance rate in our clinic had fallen back to 64.6%. A new design was used to allow for a more sustainable model. The new version of our project involved each provider in our clinic generating a pre‐made letter as they received imaging results. Results: Hepatocellular cancer screening compliance rose from 53.7% prior to any of our interventions to a high of 78.8%. Conclusions: Implementation of quality improvement measures including sending letters to patients and education of staff can significantly increase the rate of HCC surveillance.